Agriculture, economic development and the Common Market: Italian problems - PENNACCHIETTI, A.; PENNACCHIETTI, A. (PSL Quarterly Review, 2014)
The article reviews the role of the agricultural sector in the Italian economy. The recent “Ten Year Plan for the Development of Employment and Income” (the Vannoni Plan) highlights the prominent role of the agricultural investments and productivity growth in the process of Italian economic development. While the authors of the present article agree that labour should be regarded as the relatively abundant factor of production, they claim that more attention should be paid to the consequences of land scarcity. Specifically, the relative prices of agricultural products should not be expected to remain constant. JEL: N54, O13, Q17